The role of market complexity, skills and perceived usefulness on the marketing support services - Mohd Nor Hakimin Yusof; Mohamed Dahlan Ibrahim (2016)
This study aims to examine the relationships between managing market complexity, skills, and frequency of usage of marketing support services. The research was conducted through a structural equation modeling using data from 67 SMEs that operate in Malaysia. To analyze and interpret the result, a measurement model and a structural model were utilized for the main constructs – managing market complexity, skills, perceived usefulness, and the usage of marketing support services. This study found that owners, who are facing difficulties in managing their businesses, which are focused on market complexity, are more frequent users of the marketing support services. In terms of skills, SMEs with longer experience are lesser users of the marketing support services. The results from the moderator analysis failed to validate that perceived usefulness affects the relationship between managing market complexity and the frequency of usage as well as skills. The results of this study can prove to SMEs that frequent use of marketing support services can help in dealing with market complexity. The role of perceived usefulness should not be sidelined by service providers as it may have a negative impact in the long run. The findings will be of interest to researchers, policy makers, and service providers.